BIBLIOMETRIC INSIGHTS OF THREE DECADES OF CAMEL RESEARCH IN EUROPE WITH AN EMPHASIS ON COLLABORATION, RESEARCH THEMES AND EMERGING TOPICS - Mahmoud Kandeel; Maryam Mahmoud (Journal of Animal and Plant Sciences, 2025)
Camels are essential to the livelihoods of pastoral communities in dry and semi-arid regions. Although camel research in Europe is not as prominent as in camel-rearing regions, it has gained considerable interest in recent years, focusing on various aspects such as disease transmission, genetics, and the nutritional benefits of camel products. This study aims to conduct a comprehensive bibliometric analysis of camel research in Europe. It evaluates the evolution of this field, emphasizing publication trends, citation impact, collaboration networks and emerging topics.Data was sourced from the Scopus database and 1385 documents were analyzed. The analysis was conducted using VOSviewer and the Bibliometrix package in R Studio.The analysis revealed steady growth in camel research output, with a 5.51% annual increase from 1995 to 2024. A total of 5094 authors contributed to the field, with an average of 22.61 citations per document and 77.69% of documents are from international collaboration. European countries, particularly France, the UK, and Germany acted as key hubs for international collaboration. The bibliometric analysis identified five main keyword clusters in camel research in Europe. These clusters include themes such as camel physiology and veterinary medicine, the nutritional and biochemical properties of camel milk, infectious disease and antibiotic resistance, zoonotic diseases and genetics, and immunology and molecular biology, reflecting the diverse research areas within this field.Future research should focus on expanding sources, including non-English publications, and exploring advanced technologies such as genomics and AI to enhance the understanding of camel biology and its global impact.
Keywords: Camel research; Europe; bibliometric analysis; camel milk; international collaboration; VOSviewer; R Studio; Scopus